Population-level call properties of endangered Dryophytes suweonensissensu lato (Anura: Amphibia) in South Korea - Md Mizanur Rahman; Jiyoung Yun; KaHyun Lee; Seung-Ha Lee; Seung-Min Park; Choong-Ho Ham; Ha-Cheol Sung (PeerJ, 2023)
Calling is one of the unique amphibian characteristics that facilitates social communication and shows individuality; however, it also makes them vulnerable to predators. Researchers use amphibian call properties to study their population status, ecology, and behavior. This research scope has recently broadened to species identification and taxonomy. Dryophytes flaviventris has been separated from the endangered anuran species, D. suweonensis, based on small variations in genetic, morphometric, and temporal call properties observed in South Korea. The Chilgap Mountain (CM) was considered as the potential geographic barrier for the speciation. However, it initiated taxonomic debates as CM has been hardly used and is considered a potential barrier for other species. The calls of populations from both sides are also apparently similar. Thus, to verify the differences in call properties among populations of D. suweonensis sensu lato (s.l.; both of the species), we sampled and analyzed call data from five localities covering its distribution range, including the southern (S) and northern (N) parts of CM. We found significant differences in many call properties among populations; however, no specific pattern was observed. Some geographically close populations, such as Iksan (S), Wanju (S), and Gunsan (S), had significant differences, whereas many distant populations, such as Pyeongtaek (N) and Wanju (S), had no significant differences. Considering the goal of this study was only to observe the call properties, we cautiously conclude that the differences are at the population level rather than the species level. Our study indicates the necessity of further investigation into the specific status of D. flaviventris using robust integrated taxonomic approaches, including genetic and morphological parameters from a broader array of localities.